2021
DOI: 10.3389/fonc.2021.769280
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Role of PARP Inhibitors in Metastatic Triple Negative Breast Cancer. Current Scenario and Future Perspectives

Abstract: Triple negative tumors represent 15% of breast cancer and are characterized by the lack of estrogen receptors, progesterone receptor, and HER2 amplification or overexpression. Approximately 25% of patients diagnosed with triple negative breast cancer carry a germline BRCA1 or BRCA2 mutation. They have an aggressive biology, and chemotherapy has been the mainstay of treatment for a long time. Despite intensive therapies, prognosis is still poor, and many patients will eventually relapse or die due to cancer. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 99 publications
0
45
0
Order By: Relevance
“…TNBC cell lines MDA-MB-231 and Hs 578T were selected for this study, first because this phenotype is frequently associated to the lack of BRCA1 , and we thought that they could best represent a BRCA1 -deficiency context, and secondly because TNBC is the most aggressive subtype and presents limited choices of therapy ( 29 , 30 ). We used CRISPR/Cas9 to silence the BRCA1 gene in these cell lines and BRCA1 knockout (KO) single colony clones were generated.…”
Section: Resultsmentioning
confidence: 99%
“…TNBC cell lines MDA-MB-231 and Hs 578T were selected for this study, first because this phenotype is frequently associated to the lack of BRCA1 , and we thought that they could best represent a BRCA1 -deficiency context, and secondly because TNBC is the most aggressive subtype and presents limited choices of therapy ( 29 , 30 ). We used CRISPR/Cas9 to silence the BRCA1 gene in these cell lines and BRCA1 knockout (KO) single colony clones were generated.…”
Section: Resultsmentioning
confidence: 99%
“…One of the most translationally investigated families of inhibitors are the ones against Poly (ADP-ribose) polymerases (PARP), enzymes involved in DNA repair, with specific importance in TNBC with BRCA1/2 inactivation. Thus, in ongoing clinical trials, several novel combinations of PARPi with CDK4/6i, immunotherapy and/or targeted therapies, are currently being investigated for their clinical efficacy and their ability to induce synthetic lethality [ 126 , 127 ].…”
Section: Emerging Therapies and Clinical Trials For Mbcmentioning
confidence: 99%
“…Furthermore, recent studies have demonstrated that PARP inhibitors could play an important role as a maintenance treatment of advanced ovarian cancer, with improved PFS in patients with CR or PR, compared to platinum-based chemotherapy. Relying on this data, PARP inhibitors seem to deserve further investigation, in order to understand their role as a form of maintenance therapy in TNBC [ 45 ].…”
Section: Targeting Intracellular Pathwaysmentioning
confidence: 99%